The Community Structure of Picophytoplankton in Lake Fuxian, a Deep and Oligotrophic Mountain Lake - Shi, Xiaoli; Li, Shengnan; Li, Huabing; Chen, Feizhou; Wu, Qinglong (Frontiers in Microbiology, 2019)
Spatial and seasonal dynamics of picophytoplankton were investigated by flow cytometry over a year in Lake Fuxian, a deep and oligotrophic mountain lake in southwest China. The contribution of picophytoplankton to the total Chl-a biomass and primary production were 50.1% and 66.1%, respectively. Picophytoplankton were mainly composed of phycoerythrin-rich picocyanobacteria (PE-cells) and photosynthetic picoeukaryotes (PPEs). PPEs were dominant in spring, reaching a maximum cell density of 3.0 × 104 cell mL-1, while PE-cells were prevalent in other seasons. PE-cell abundance was relatively similar throughout the year, except for a decrease in summer during the stratification period, when nutrient concentration was low. High-throughput sequencing results from the sorted samples revealed that Synechococcus was the major PE-cell type, while Chrysophyceae, Dinophyceae, Chlorophyceae, Eustigmatophyceae, and Prymnesiophyceae were equally important PPEs. In spring, PPEs were mainly composed of Chlorophyceae and Trebouxiophyceae, while in summer, their dominance was replaced by that of Chrysophyceae and Prymnesiophyceae. Eustigmatophyceae and Chlorophyceae became the major PPEs in autumn, and Dinophyceae became the most abundant in winter. Single Microcystis cells were detected mainly in summer in the south, suggesting a potential deterioration of the water quality in Lake Fuxian.